The Effect of Compensation and Work Experience on Employee Productivity at CV Lutfi Bangun Persad - Sugeng Hariyadi; Fadia Budi Cahyono; Javan Agustian Setyagraha; Vera Firdaus (Green Publisher Indonesia, 2025)
Inconsistent effects of compensation and work experience on employee performance, coupled with ongoing productivity challenges at CV. Lutfi Bangun Persada, raise critical questions about the drivers of workforce efficiency. This study aims to examine the following influences, (1) compensation and work experience on work productivity, (2) compensation on work productivity, (3) work experience on work productivity. The population in this study were all employees working at CV. Lutfi Bangun Persada, totaling 39 employees. Based on the characteristics of the problem studied, this study uses a causal quantitative research design. Data collection techniques in this study were document recording and questionnaires. The data analysis technique used was multiple linear regression analysis techniques. In this study, a Likert scale was used. By using this scale, researchers can measure the attitudes, opinions, and perceptions of respondents. The results of the study showed that compensation and work experience influenced work productivity, compensation influenced work experience, compensation influenced work productivity, and work experience influenced work productivity.